SAMANID DYNASTY DEVELOPMENT, GOVERNMENT ADMINISTRATION, RACE AND SCIENCE - Meirison, Meirison; Muzakki, Muhammad Harir (Journal of Islamic Studies and Humanities, 2021)
This paper aims to describe the worth noting that the Samanids had prominent civil and political roles. During their reign, writing appeared in the Persian language and the Arabic language. The Samanid era witnessed an industrial renaissance manifested in ceramics, paper, carpets, and textiles. From a political point of view, the Samanids defended the eastern border region and extended Islamic influence to the countries of the Turks. They never departed from the subordination of the Abbasid Caliphate in Baghdad. We conducted a literature study to discuss the development of the Samanid dynasty, starting from its power, administration, and distinction in science and the race that developed in this Sunni dynasty. He also endeavoured to bring scholars to the presence of his kingdom and honoured them, benefited and rewarded them. During the years of his rule, which exceeded thirty years, this prince was just, benevolent, and wise. The cities of his state flourished, namely: Nishapur, Merv, Balkh, Bukhara, Samarkand, and others. But after the death of Prince Ismail al-Samani, a conflict erupted between members of the Samanid house in greed for power. The influence of politicians increased, and the weakness of the state began to appear and gradually increase